Legal Construction of The Green Economy in Enviromental Management in The Era of Climate Change - Satriya Nugraha; Rosmawiah (Proceeding International Conference on Digital Education and Social Science, 2024)
Climate change is an urgent global challenge requiring innovative approaches to environmental management. One such approach that is gaining traction is the green economy, which integrates economic growth with ecological sustainability. This research aims to analyze the legal construction of the green economy in the context of environmental management in Indonesia, particularly in addressing the impacts of climate change. This study employs a normative legal research method with legislative and conceptual approaches, exploring national regulations such as Law No. 32 of 2009 on Environmental Protection and Management, as well as policies related to a low-carbon economy, including carbon taxes and renewable energy incentives. The findings indicate that although relevant regulations exist, their implementation still needs to be improved, such as the lack of economic incentives for businesses to transition to environmentally friendly practices and weak law enforcement. Within the framework of the green economy, there is a need to strengthen legal instruments that promote innovation, investment, and cross-sector cooperation. This study recommends further integration of environmental and economic policies through a progressive legal approach, which emphasizes not only the mitigation of climate change impacts but also the protection of the rights of vulnerable communities and ecological justice. Thus, the legal construction of the green economy can become a key pillar in building sustainable environmental management in the era of climate change.